Active online learning with remote sensing data in higher education - Moldamurat, Khuralay; Atanov, Sabyrzhan; Nagymzhanova, Karakat; Spada, Luigi La; Kalmanova, Dinara; Tazhikenova, Sapiya; Zhanzhigitov, Syrym; Zhakupov, Altynbek; Yessilov, Assylkhan; Bakyt, Makhabbat (Institute of Advanced Engineering and Science, 2025)
The increasing popularity of online learning has created a need for effective methods to enhance educational quality. This study addresses this need by developing and evaluating an active online learning model incorporating remote sensing data (RSD). The study included a pedagogical experiment with 181 students divided into control and experimental groups. The model included an interactive database, a web portal with tools for processing and visualizing RSD, and the implementation of active learning methods. Data were collected through testing, analysis of completed projects, and questionnaires. Quantitative and qualitative analysis methods were used to process the data. The pedagogical experiment showed that the model improved students’ average scores, increased the number of students with high levels of knowledge acquisition, and enhanced motivation. Thus, the use of RSD and active learning methods in online education is a promising approach to improve the quality of the educational process and foster students’ digital competence.